2022
DOI: 10.34172/jhp.2022.20
|View full text |Cite
|
Sign up to set email alerts
|

Potential pharmacokinetic and pharmacodynamic herb-drug interactions of Andrographis paniculata (Burm. f.) and andrographolide: A systematic review

Abstract: Introduction: Herb–drug interactions (HDIs) in pharmacokinetics and pharmacodynamics can occur when natural compounds are used in combination with drugs. This study aimed to review the potential interaction of Andrographis paniculata (Burm. f.) extract (APE) and its primary compound andrographolide (AND) with several drugs exhibiting various pharmacological activities.Methods: In this systematic review, articles were collected from international databases such as PubMed, Science Direct, Springer Link, and Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Table (1) indicates that oral administration with a 100mg / kg dose of A. paniculata extract led to no significant differences in the rate of liver enzymes (ALP, ALT and AST), and this is agreement with (Owoade et al, 2022;Salunkhe & Patil (2018;Shi etal., 2020;Dey etal., 2020;Nasir etal., 2013) The absence of a significant difference in liver enzymes in the current paper may be due to the role of the plant used as an effective drug in treating many different diseases and disorders to the organs, such as the liver (Sundhani et al, 2022), During the study period, BHT caused the harmful effect on the liver through the production of free radicals and stimulation of oxidative stress. It has been proven that the aqueous extract of A. paniculata played an effective role in scavenging free radicals, as this plant contains many active active compounds such as andrographiold, Andrographolide, Andographoside and Newandrographolide in addition to many other important active compounds that scavenge free radicals and protect the liver from oxidative stress caused by harmful substance and thus regulate the work of liver enzymes (Saunkhe & Patil, 2018(Benny et al, 2021).…”
Section: Effects Of a Paniculata On Alp Alt And Astmentioning
confidence: 82%
“…Table (1) indicates that oral administration with a 100mg / kg dose of A. paniculata extract led to no significant differences in the rate of liver enzymes (ALP, ALT and AST), and this is agreement with (Owoade et al, 2022;Salunkhe & Patil (2018;Shi etal., 2020;Dey etal., 2020;Nasir etal., 2013) The absence of a significant difference in liver enzymes in the current paper may be due to the role of the plant used as an effective drug in treating many different diseases and disorders to the organs, such as the liver (Sundhani et al, 2022), During the study period, BHT caused the harmful effect on the liver through the production of free radicals and stimulation of oxidative stress. It has been proven that the aqueous extract of A. paniculata played an effective role in scavenging free radicals, as this plant contains many active active compounds such as andrographiold, Andrographolide, Andographoside and Newandrographolide in addition to many other important active compounds that scavenge free radicals and protect the liver from oxidative stress caused by harmful substance and thus regulate the work of liver enzymes (Saunkhe & Patil, 2018(Benny et al, 2021).…”
Section: Effects Of a Paniculata On Alp Alt And Astmentioning
confidence: 82%
“…The aerial parts have been documented in the treatment of the common cold, hypertension, malaria, and snakebites ( Okhuarobo et al, 2014 ). A. paniculata has the potential for HDIs, particularly when taken in combination with drugs metabolized by CYP3A, CYP2C9, and CYP2C19, through both induction and inhibition ( Sundhani et al, 2022 ). Balap et al (2017) reported that co-administration of A. paniculata extract with naproxen, a CYP2C9 substrate in humans, decreased systemic exposure to naproxen in rat models.…”
Section: Resultsmentioning
confidence: 99%
“…APE exhibits glucose-lowering efficacy in rats by increasing the mRNA and protein expression of GLUT-4 and insulin expression in pancreatic beta cells [ 56 , 57 ]. A study reported evidence of an increase in the pharmacological action of the medicine (synergistic effect) when the anti-inflammatory agents etoricoxib and naproxen were combined with APE [ 58 ].…”
Section: Discussionmentioning
confidence: 99%